2010
DOI: 10.1182/blood-2009-04-218842
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the JAK2 inhibitor INCB16562 in a murine model of MPLW515L-induced thrombocytosis and myelofibrosis

Abstract: IntroductionPolycythemia vera (PV), essential thrombocytosis (ET), and primary myelofibrosis (PMF) are classified as BCR-ABL Ϫ myeloproliferative neoplasms (MPNs), typified by clonal proliferation of 1 or more myeloid lineages. 1,2 There are approximately 130 000 to 150 000 patients with MPN in the United States, which makes these disorders among the most common hematopoietic malignancies. 3 Patients with MPN are at high risk for several disease-related complications, including bleeding, thrombosis, splenomega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 38 publications
4
61
0
Order By: Relevance
“…We also performed Western blot analysis of JAK2 protein levels in normal and MPLW515L splenocytes after a single dose of PU-H71. Consistent with the pharmacokinetic data, we observed potent degradation of JAK2 but does not result in reduction in the size of the malignant clone (55). We therefore wished to determine whether HSP90 inhibition with PU-H71 was able to reduce mutant allele burden in this model.…”
Section: Pu-h71 Is Retained In Mpn Cells Leading To Degradation Of Jmentioning
confidence: 48%
“…We also performed Western blot analysis of JAK2 protein levels in normal and MPLW515L splenocytes after a single dose of PU-H71. Consistent with the pharmacokinetic data, we observed potent degradation of JAK2 but does not result in reduction in the size of the malignant clone (55). We therefore wished to determine whether HSP90 inhibition with PU-H71 was able to reduce mutant allele burden in this model.…”
Section: Pu-h71 Is Retained In Mpn Cells Leading To Degradation Of Jmentioning
confidence: 48%
“…27,28 We hypothesized that Jak2 loss in PLTs and MKs would compromise TPO internalization and maintain high steady state TPO despite thrombocytosis. We assessed TPO levels in Pf4-Cre-positive Jak2 f/f mice, controls, and mice expressing MPLW515L, 29 which develop a similar extent of thrombocytosis and MK expansion as Pf4-Cre-positive Jak2 f/f mice. Serum TPO was markedly reduced in MPLW515L mice (TPO 230 1/2 37 pg/mL in MPLW515L vs 2787 1/2 204 pg/mL in controls, P , .0001), but not in Pf4-Cre-positive Jak2 f/f mice (TPO 2524 1/2 230 pg/mL, P , .0001) (n 5 8 to 13 mice/group; Figure 2I).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro data of both studies show sufficient sensitivity and specificity of two different smallmolecule JAK2 inhibitors, pathway specificity in vitro and in vivo, as well as response to treatment, such as improved platelet counts, WBC, body weights, decreased splenic weights; however both studies were not able to show elimination of the malignant clone. 11 A significant proportion (B50%) of ET and MF patients lack the JAK2V617F mutation. 1,2,[12][13][14] The MPLW515L and JAK2 Exon 12 alleles account for an additional B10% and B2%, respectively, of the JAK2V617F-negative patients 4,14 and less commonly TET2, ASXL1, CBL, IDH and IKZF1.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 In contrast, robust thrombocytosis is induced in the MPLW515L murine BMT model. 4,11 We therefore used this system to evaluate platelet response to the JAK2-specific smallmolecule inhibitor EXEL-8232. We designed these studies by treating animals for 28 days with EXEL-8232 from day 10 post BMT and demonstrated dose-dependent responses to therapy as well as insights into potential side effects.…”
Section: Discussionmentioning
confidence: 99%